2021
DOI: 10.1108/ejmbe-11-2019-0213
|View full text |Cite
|
Sign up to set email alerts
|

Innovative outcome through exploration and exploitation – Enablers, barriers and industrial property

Abstract: PurposeThis research aims to study the effect of R&D (research and development) enablers and barriers as well as industrial property on exploration, their influence on exploitation and finally the possible impact on innovative outcome (IO) as a result variable. The IO can be defined as the orientation towards new or improved products, services and processes, as well as towards penetration and greater market share, which the company has obtained as a result of innovative processes.Design/methodology/approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 105 publications
(125 reference statements)
1
4
0
2
Order By: Relevance
“…The study also contributes to the literature by providing an understanding on the relationship between exploitation and exploration. The findings are in line with the previous studies that find the impact of exploitation on exploration (Isobe et al, 2004;Piao & Zajac, 2016;Vargas et al, 2022).…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…The study also contributes to the literature by providing an understanding on the relationship between exploitation and exploration. The findings are in line with the previous studies that find the impact of exploitation on exploration (Isobe et al, 2004;Piao & Zajac, 2016;Vargas et al, 2022).…”
Section: Introductionsupporting
confidence: 93%
“…‘Doing things better’ through exploitation might relieve the tensions among members when ‘doing better things’ via exploration (Brix, 2019, p. 13), and each of these non‐substitutable dimensions can be complementary when increasing the performance of each other (Lin & Ho, 2016). Therefore, a focus on exploitation can be supportive for the companies' adaptability to the changes and impels exploration (Piao & Zajac, 2016), and higher exploitation capabilities can help companies to obtain better exploration skills (Isobe et al, 2004; Vargas et al, 2022). Based on this discussion, it can be suggested thatH5 Exploitation positively affects exploration.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Finalmente, se hallaron barreras de mercado en economías desarrolladas donde se presenta incredulidad en innovaciones exitosas y protección de propiedad intelectual (Vargas, Lloria et al, 2022). El mercado no ofrece una garantía eficaz que permita a los empresarios o dueños de dichas ideas innovadoras proteger su idea, pues los trámites son demorados y no impiden que se copie la idea (Hashimy et al, 2021).…”
Section: Resultsunclassified
“…R&D firms should be involved in sufficient exploitation to guarantee its current viability while devoting sufficient attention to exploration to ensure the organisation's future viability (Levinthal & March, 1993). In addition, Vargas et al (2021) also reported that R&D firms should use their knowledge in the search for improvements within an established framework (i.e., exploitation) to pursue an orientation based on refreshing knowledge towards exploration. Some studies have used the notion of ambidexterity to refer to the balance between exploration and exploitation (D'Souza et al, 2017;Hill & Birkinshaw, 2014;O'Reilly & Tushman, 2013).…”
Section: Km Practices: Knowledge Exploration and Knowledge Exploitationmentioning
confidence: 99%